2017
DOI: 10.1142/s0218271817300233
|View full text |Cite
|
Sign up to set email alerts
|

Testing theories of gravity and supergravity with inflation and observations of the cosmic microwave background

Abstract: Abstract. Cosmological and astrophysical observations lead to the emerging picture of a universe that is spatially flat and presently undertaking an accelerated expansion. The observations supporting this picture come from a range of measurements encompassing estimates of galaxy cluster masses, the Hubble diagram derived from type-Ia supernovae observations, the measurements of Cosmic Microwave Background radiation anisotropies, etc. The present accelerated expansion of the universe can be explained by admitti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 258 publications
(204 reference statements)
0
12
0
Order By: Relevance
“…For example, considering the f (R) gravity, with f (R) = R + a R n , we have found that IceCube data and DM relic abundance can be explained provided n < 1, However, such a value is not favored by recent Planck release, which require n > 1 (and in fact the Starobisnky model n = 2 is one of the favorite candidate for Inflation) [114,115]. Results here discussed do not allow to distinguish between f (T ) and BD theories of gravity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, considering the f (R) gravity, with f (R) = R + a R n , we have found that IceCube data and DM relic abundance can be explained provided n < 1, However, such a value is not favored by recent Planck release, which require n > 1 (and in fact the Starobisnky model n = 2 is one of the favorite candidate for Inflation) [114,115]. Results here discussed do not allow to distinguish between f (T ) and BD theories of gravity.…”
Section: Discussionmentioning
confidence: 98%
“…The signal of inflation is in the cosmic microwave anisotropy spectrum while the only experimental evidence of the radiation era is the successful predictions of big-bang nucleosynthesis (BBN) which occurs around T∼ 1 MeV at t ∼ 1 s. Observations from Type Ia Supernovae [32,33], CMB radiation [34,35], and the large scale structure [36,37], suggest that there are strong evidences that the present cosmic expansion of the Universe is accelerating. The latter is ascribed to the existence of Dark Energy (DE), an exotic form of energy characterized by a negative pressure that at late times dominates over the cold and dark matter, driving the Universe to the observed accelerating phase, and new ingredients, such as DM and Dark Energy (DE), are required [38][39][40][41][42][43][44][45][46][47][48][49][50]. Both inflation and dark energy have motivated the extension of Einstein's theory to a general f (R) theory [51].…”
Section: Introductionmentioning
confidence: 99%
“…the N 1 scattering rates in which the Higgs φ processes in tand s-channels are involved), and Γ W is the washout-rate. The quantities Ω = D, S, W are proportional to λ † λ, so that the reduced rates entering (12) are such that [52] (12), are dependent on A(T). However, in this paper we are mainly interested to fulfill the conditions allowing the out-of-equilibrium, and the consequent constraints on the parameter spaces of the non-standard cosmology, therefore the numerical analysis of the N 1 and N B−L quantities are beyond the scope of the present paper, and will be faced elsewhere (in the regime to which we are interested in this paper, i.e., A(T) ∼ T (ν = 1) and A(T M 1 ) ∼ O(10 − 10 2 ), see next Section, one gets H(z)…”
Section: Kinetic Equationsmentioning
confidence: 99%
“…Modified theories of gravity have been proposed in the last years as a possible solution of the shortcomings related to the Cosmological Standard Model, based on General Relativity (GR). This is the case, for example, of higher order curvature invariants than the simple Ricci scalar R that allow to get inflationary behaviors, removing the primordial singularity, and to explain the flatness and horizon problems [1] (see also [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]). This approach and, of course, all those related to it, are fundamentally motivated by the fact that, at high curvature regimes, further curvature invariants have to be considered for constructing self-consistent effective actions in curved spacetime [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…From a fundamental physics point of view, such curvature invariants are derived as quantum corrections from renormalisation of gravity in curved spacetime [65]. Other curvature invariants, as R μν R μν , R μνσρ R μνσρ have also been taken into account in literature [66][67][68][69][70][71][72], in particular the Gauss-Bonnet topological invariant G which is related to the emergence of the trace anomaly in curved spacetime [65,73]. In general, if both R and G are present in the gravitational action, all the curvature budget is considered, if we do not take into account further derivative terms like R and others [8].…”
Section: Introductionmentioning
confidence: 99%